iSim — An Integrated Sar Product Simulator for System Designers and Researchers - Koo, V. C.; Lim, C. S.; Chan, Y. K. (VSP BV, 2007)
Traditionally, design and development of SAR systems have been expensive and time-consuming tasks. This paper introduces an integrated SAR product simulator, called iSIM, which is developed to assist system designers and researchers in simulating and analysing SAR related products. The iSIM is implemented by using Matlab (R) software. Generally, it consists of four basic modules to perform SAR system design, simulation, processing, and image displays. It is a modular-based simulator with various independent modules that share a pool of data files. The generated data format is a simplified version of the CEOS (Committee of Earth Observations Satellites) standard on SAR data, set. A motion error simulation is used as an example to illustrate the usefulness of the iSIM for SAR communities.